Five-Year Outcomes after Off-Pump or On-Pump Coronary-Artery Bypass Grafting - Lamy, André; Devereaux, P.J; Prabhakaran, Dorairaj; Taggart, David P; Hu, Shengshou; Straka, Zbynek; Piegas, Leopoldo S; Avezum, Alvaro; Akar, Ahmet R; Lanas Zanetti, Fernando; Jain, Anil R; Noiseux, Nicolas; et al. (The New England journal of medicine, 2016)
After 5 years of follow-up in this trial, the rates of the composite outcome of death, stroke, myocardial infarction, renal failure, or repeat revascularization were similar with off-pump and on-pump CABG. There was also no significant difference in cost or in quality of life. Coronary-artery bypass grafting (CABG) reduces the risk of death in patients with extensive coronary artery disease. 1 CABG is usually performed with the use of a cardiopulmonary bypass (on-pump CABG). With this approach, perioperative mortality is approximately 2%, with an additional 5 to 9% of patients having myocardial infarction, stroke, or renal failure requiring dialysis. The technique of performing CABG on a beating heart (off-pump CABG) was developed to decrease the risk of perioperative complications and to improve long-term outcomes; some complications, both perioperative and long term, may be related to the use of cardiopulmonary bypass and to cross-clamping of the . . .